High temperature corrosion of SiC-CaAl12O19 composite refractory by coal slag. (September 2022) - Si, Yaochen; Li, Hongxia; Sun, Honggang; Xia, Miao; Du, Yihao; Shang, Xinlian; Zhao, Shixian
Abstract: Corrosion processes of SiC-CaAl12 O19 (CA6 ) composite refractory were carried out by both static crucible test and rotary drum test at 1500 °C and 1600 °C under a reducing atmosphere, respectively. The corrosion mechanism of the SiC-CA6 refractory was analyzed by means of X-ray diffraction(XRD) and scanning electron microscope(SEM). The results show that the corrosion temperature and condition had significant influence on the slag resistance of the SiC-CA6 refractory. But no matter which corrosion methods and which temperatures under the condition of this experiment, the SiC-CA6 refractory exhibited good penetration resistance even though a little corrosion appeared at a higher temperature. During the corrosion process, most of Fe containing oxide in slag could be reduced by CO in atmosphere and SiC in samples to form Fe-Si metal alloys, which precipitated at the interface between the slag and composites. The penetrated slag could react with the SiO2 produced by SiC oxidation and the CA6 matrix to form CaAl2 Si2 O8 and corundum, filling the pore inside the samples and causing the densification of the reaction layer. Because of the reaction between infiltrated slag and SiC-CA6 refractory, the composition and properties of local slag changed and inhibited the further penetration. Highlights: High temperature corrosion processes of SiC-CaAl12 O19 (CA6 ) composite refractory were carried out. The corrosion mechanism of the SiC-CA6 refractory was analyzed at evaluated experiment conditions. The corrosion resistance of SiC-CA6 refractory was compared with the traditional high chromia refractory.